Optimizing Prompt Engineering for AI-Based Logo Generation Using Response Surface Methodology - Shermay; Syaeful Anas Aklani; Muhamad Dody Firmansyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This research developed an optimized prompt engineering framework for AI-based logo generation using Response Surface Methodology (RSM) with Central Composite Design (CCD). Despite rapid AI adoption, users face challenges in communicating design intent effectively, leading to inconsistent outputs. This study systematically tested 47 prompt combinations across five variables: prompt clarity, detail level, thematic description, visual elements, and color specification. The optimization identified eight critical components forming a structured template: Main Design Focus, Detail Elements, Thematic Style, Primary Colors, Complementary Colors, Rewording, Layout Size, and Element Limit. Experimental validation with 30 graphic designers demonstrated substantial improvements over unstructured prompts: visual consistency increased from 65% to 87%, iteration efficiency improved by 48.5% (from 6.6 to 3.4 attempts), and user satisfaction rose from 58% to 82%. Both manual designers and AI-experienced users successfully applied the framework with comparable effectiveness. This research contributes a systematic, optimization-based approach to prompt engineering in creative AI applications and provides a practical framework enhancing accessibility for non-technical users while maintaining professional quality standards in logo desin.